the article Refleksi Filosofis Transformasi Menuju Masyarakat Terbuka: Wawasan Liberalisme Indonesia Perspektif Francis Fukuyama: Philosophical Reflections on Transformation Towards an Open Society: Insights into Indonesian Liberalism from Francis Fukuyama's Perspective - Semit, Marianus Elki; Pandor, Pius (Undiksha, 2025)
The focus of this writing explores the transformation towards an open society in the context of Indonesia based on Francis Fukuyama's perspective on liberalism. This research investigates the extent to which Fukuyama's perspective on liberalism can serve as a foundation for the transformation of Indonesian society. It is hoped that Fukuyama's thoughts on liberalism provide a critical insight into the relevance and contribution of these ideas to the transformation of Indonesian society. The implementation of liberal ideas in Indonesia, in my opinion, requires a lengthy process. Society continues to linger in a state of stagnation, feeling comfortable in their own complacency. The community remains shackled and bound, with freedom of movement being severely restricted. Perhaps the ideas and concepts of Fukuyama can have a significant impact in the Indonesian context, despite facing certain challenges and obstacles, meaning there is movement towards individual and collective well-being gradually, step by step.The methodology of this academic work involves a literature review and the results obtained from attending a seminar on the philosophy of liberalism. The findings of this research provide a mapping of the results of the analysis and its implications for the future of Indonesia, along with recommendations to optimize the potential towards the desired open society.